The viewing of a 'Bloodcurdling' horror movie increases platelet reactivity: A randomized cross-over study in healthy volunteers. Issue 182 (October 2019) - van Diemen, J.J.K.; van Dijk, A.; Racca, C.; Knol, T.; Bonten, T.N.; Numans, M.E.; Fuijkschot, W.W.; Smulders, Y.M.; Thijs, A.
Abstract: Background: Epidemiological studies have suggested an increased risk of cardiovascular events (CVE) during acute stressful and/or frightful moments. A possible explanation for this could be an effect of acute stress on hemostasis. A recent study demonstrated an increase in factor VIII after watching a horror movie. Primary hemostasis, however, is thought to play a more prominent role in the etiology of CVE. The objective of this study was therefore to assess the influence of viewing a 'bloodcurdling' horror movie on platelet reactivity in healthy volunteers. Methods: We performed a randomized cross-over study in healthy adults. Subjects were allocated to two movies in random sequence: a horror and a control movie. Blood was drawn at baseline and after 24 min of viewing time. The primary endpoint was the change in Platelet Function Analyzer® Closure Time (Δ PFA-CT) after watching the movie. Results: In total, 20 participants, aged 18–30 years, completed the study protocol. The delta PFA-CT was statistically significantly shorter with a mean in the delta difference of −9.7 s (SEM 4.0, 95% C.I. −18.0 to −1.3) during the horror movie versus the control movie. The Light Transmission Aggregometry endpoints were in line with the PFA-CT, albeit only the highest level of Arachidonic Acid agonist demonstrated a statistically significant mean difference in the delta of aggregation of 13.15% (SEM 7.0, 95% C.I. 1.6–27.9). Conclusion: A 'blood curdling' horror movie increases platelet reactivity. These data are supportive of a role of platelet reactivity in acute stress induced cardiovascular event risk. Highlights: There is an increase of cardiovascular events during acute stressful moments. Primary hemostasis plays a prominent role in the etiology of CVE. A horror movie was used to simulate psychological stress in a research setting. A horror movie increases platelet reactivity. These results help elucidate the profound physiological effects of stress.